Efforts to Maintain Artifacts in The Langkat District Regional Museum: Upaya Pemeliharaan Artefak di Museum Daerah Kabupaten Langkat - Annisa; Yusra Dewi Siregar (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
Artifacts are historical relics that contain important information about various aspects of life. Museums, which serve as custodians of historical objects, are required to optimize this role, especially concerning their artifact collections. This research was conducted at the Langkat Regency Regional Museum, aiming to identify the efforts made in preserving artifact collections and the challenges faced by the museum's management in these preservation efforts. This study is descriptive in nature, utilizing a qualitative approach, with data collected through interviews, observations, and document studies. The informants in this study included the museum director and staff members working as managers at the Langkat Regency Regional Museum. The findings of this research indicate that preservation activities at the Langkat Regency Regional Museum have been implemented as part of preventive conservation efforts to prevent damage to artifacts and extend their lifespan. The challenges faced by the museum's management in their preservation efforts include a lack of human resources (HR) and limited budget.